2010
DOI: 10.1039/b924832c
|View full text |Cite
|
Sign up to set email alerts
|

A graphene-based fluorescent nanoprobe for silver(i) ions detection by using graphene oxide and a silver-specific oligonucleotide

Abstract: A fluorescence sensor for Ag(I) ions is developed based on the target-induced conformational change of a silver-specific cytosine-rich oligonucleotide (SSO) and the interactions between the fluorogenic SSO probe and graphene oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
215
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 447 publications
(223 citation statements)
references
References 30 publications
(26 reference statements)
5
215
1
Order By: Relevance
“…8,18 The EIS technique was used to monitor the charge transfer resistance of the redox couple on the RGO-modified electrode surface after the immobilization of the probe hp-DNA. The introduction of an hp-DNA probe layer sterically hindered the redox couple, Fe(CN) 6 3-and Fe(CN) 6 …”
Section: -mentioning
confidence: 99%
“…8,18 The EIS technique was used to monitor the charge transfer resistance of the redox couple on the RGO-modified electrode surface after the immobilization of the probe hp-DNA. The introduction of an hp-DNA probe layer sterically hindered the redox couple, Fe(CN) 6 3-and Fe(CN) 6 …”
Section: -mentioning
confidence: 99%
“…While the majority of graphene based sensors employ electrochemical detection methods, a graphene based fluorescent nanoprobe for detection of silver ions has also been developed (163). Fluorescein labeled silver specific oligonucleotides (SSO) were prepared.…”
Section: Carbon Nanotubes and Graphenementioning
confidence: 99%
“…Ag + can selectively interact with cytosine bases (C) to form strong and stable C-Ag + -C complexes. [10][11][12][13][14][15][16][17][18] Based on this fact, nanomaterial has been introduced for silver(I) ion detection. For example, Li et al reported a graphene-based fluorescent DNA sensor for silver(I) ions detection.…”
Section: Introductionmentioning
confidence: 99%